2010
DOI: 10.1158/0008-5472.can-09-1876
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl Hydroxylases 2 and 3 Act in Gliomas as Protective Negative Feedback Regulators of Hypoxia-Inducible Factors

Abstract: Adaptive responses to hypoxia in tumors are transcriptionally regulated by the hypoxia inducible factors (HIF-1α/HIF-2α), which are tightly controlled by the HIF-prolyl hydroxylases (PHD). Hypoxia induces expression of the PHD2 and PHD3 proteins in tumors but the pathobiological significance of these events is uncertain. Here, we show that PHD2 and PHD3 induction acts within a negative feedback loop to limit the hypoxic HIF response. In glioblastomas, PHD2 and PHD3 are hypoxia-inducible in vitro and expressed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
99
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 40 publications
9
99
2
Order By: Relevance
“…The symbol, name, relationship with mTOR and the respective references are provided in this table. al. 2002), is increased in hypoxic condition (Henze et al 2010). On the other hand, p53 expression was not increased in the L group.…”
Section: Discussionmentioning
confidence: 82%
“…The symbol, name, relationship with mTOR and the respective references are provided in this table. al. 2002), is increased in hypoxic condition (Henze et al 2010). On the other hand, p53 expression was not increased in the L group.…”
Section: Discussionmentioning
confidence: 82%
“…The Egln3 protein is unregulated in numerous types of human cancer, including pancreatic cancer (32) and glioblastoma (27). The function of Egln3 is dependent on prolyl hydroxylase activity through which it hydroxylates a number of targets, including Hif-2α (19) and other α subunits of Hif, larger subunits of RNA polymerase II, pyruvate kinase M2 and β2-adrenergic receptors (11,14,(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of Hif-2α is also associated with proapoptotic activity (22). However, the role of Egln hydroxylases in cancer biology is poorly understood, with two varying hypotheses currently presented; one suggesting that they function as tumor suppressors and the other favoring their contribution towards tumor aggressiveness (23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…In further support of a role for Hif2a in sympathetic development, mice lacking the HIF prolyl hydroxylase PHD3 displayed an increased number (but reduced functionality) of sympathetic cells in the adrenal medulla, carotid body and the superior cervical ganglia due to reduced apoptosis (Bishop et al 2008). A reasonable assumption based on the role of PHD3 in targeting HIFs for degradation is that HIF protein levels in general would be higher in PHD3 -/-animals, and in vitro studies have suggested that PHD3 is more important in regulation of HIF-2α than HIF-1α (Appelhoff et al 2004;Henze et al 2009). Indeed, the sympathetic phenotype of Phd3 -/-mice was intriguingly reversed by crossing animals with heterozygous Hif2a +/-(but not Hif1a +/-) mice, again indicating that proper control of Hif2a expression is crucial for normal SNS development (Bishop et al 2008).…”
Section: Hif-2 During Normal Sympathetic Nervous System (Sns) Developmentioning
confidence: 99%